2004
DOI: 10.1097/00008571-200411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Complex haplotype structure of the human GNAS gene identifies a recombination hotspot centred on a single nucleotide polymorphism widely used in association studies

Abstract: The alpha subunit of the heterotrimeric G protein Gs (Gsalpha) is involved in numerous physiological processes and is a primary determinant of cellular responses to extracellular signals. Genetic variations in the Gsalpha gene may play an important role in complex diseases and drug responses. To characterize the genetic diversity in this locus, we resequenced exons and flanking introns of the gene in 44 genomic samples and analysed the haplotype structure of the gene in an additional 50 African-Americans and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The GNAS1 T393C polymorphism is located in exon 5 within a recombination hotspot that is in linkage equilibrium with two haplotype blocks, one located 5 ¶ and one 3 ¶ of the T393C polymorphism (13,35). Moreover, although synonymous, the T>C substitution at position 393 could be calculated to change mRNA folding (13).…”
Section: Discussionmentioning
confidence: 99%
“…The GNAS1 T393C polymorphism is located in exon 5 within a recombination hotspot that is in linkage equilibrium with two haplotype blocks, one located 5 ¶ and one 3 ¶ of the T393C polymorphism (13,35). Moreover, although synonymous, the T>C substitution at position 393 could be calculated to change mRNA folding (13).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, CC genotypes presented at an advanced pathologic stage at first diagnosis (P = 0.024; see Table 1). The T393C polymorphism is located within a recombination hotspot which was supposed to be in linkage equilibrium with two haplotype blocks, one 5V and one 3V of the T393C polymorphism (17). Therefore, one SNP (T2291C) of the 5V block and one SNP (T18830C) of the 3V block were chosen to analyze linkage disequilibrium; a weak but significant linkage disequilibrium was found between each SNP and the T393C polymorphism (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we investigated a potential association between genotypes of the T393C polymorphism and survival in a series of patients suffering from sporadic colorectal carcinoma. It was recently suggested that the T393C polymorphism lies within a recombination hotspot surrounded upstream and downstream within the same gene by two haplotype blocks (17). The second aim of the study was therefore to investigate possible associations of one SNP from the 5Vblock (T2291C, dbSNP rs6026584) and one SNP from the 3V block (T18830C, dbSNP rs234628) with outcome from colorectal cancer.…”
mentioning
confidence: 99%
“…GNAS belongs to the class of imprinted genes, and some transcripts are transcribed maternally, paternally, and biallelic, partially in a tissue-dependent fashion (for review, see Weinstein et al, 2004Weinstein et al, , 2006. The rs7121 is located in a recombination hotspot of GNAS centered on exons 4 and 5, separating two haploblocks (Yang et al, 2004). It has been demonstrated that rs7121 is in close linkage disequilibrium with rs6123837, a polymorphism located in the putative promoter region of the start exon, that is involved in the generation of G␣ S (Frey et al, 2008).…”
Section: ␤-Antagonistmentioning
confidence: 99%